Pulmonary Hypertension Surveillance – Saudi Arabia, 2014 - Al-Saikhan, Fahad I; Abd-Elaziz, Mohamed A; Al-Shdefat, Ramadan I.; Ahsan, Fakhrul (Asian Journal of Biological and Life Sciences, 2015)
Pulmonary arterial hypertension (PAH) is a progressive life-threatening disease. Information about the incidence and prevalence of PH in Saudi Arabia remains limited.The aims of the present study were to estimate prevalence of PAH and compare clinical characteristics and the demographic of PH due to various causes in a Saudi population Newly diagnosed cases of PH [defined as the mean pulmonary artery pressure > 25 mmHg at right heart cauterization (RHC)] were prospectively collected at a single tertiary care hospital from January 2013 and June 2014. Detailed clinical, demographic data and hemodynamic parameters were collected at the time of diagnosis. Results of the total 925 patients who underwent RHC, 368 were identified as having PH. At diagnosis the mean age was 37.8 ± 12.8 years, and there was a female preponderance of 62.4%. One hundred sixty five of the patients (44.8%) were classified as Idiopathic pulmonary arterial hypertension, ninety three (25.2%) as Congenital heart disease-associated pulmonary arterial hypertension, eighty nine (24.1%) as a Connective tissue disease-associated pulmonary arterial hypertension, twelve (3%) as Heritable pulmonary arterial hypertension), and nine (2.4%) as Portal hypertension-associated pulmonary arterial hypertension. Most of the patients were in stage III pulmonary hypertension. This data emphasize the current status of pulmonary arterial hypertension in Saudi Arabia. Patients having pulmonary arterial hypertension are much younger than patients described in other international records, but the course of the disease is still detected lately. A majority of patients showed severe functional and hemodynamic impairments. Screening of patients for PAH will help in early diagnosis and therapeutic intervention before significant end-organ damage occurs.
Keywords: Hemodynamics; prevalence; pulmonary arterial hypertension; Saudi Arabia